Associations of platelet indices with proteinuria and chronic kidney disease - Kemec, Zeki; Demir, Mustafa; Gurel, Ali; Demir, Fadime; Akin, Selcuk; Dogukan, Ayhan; Koca, S. Serdar (Sage Publications Ltd, 2020)
Objectives Platelet (PLT) indices are predictive in many diseases and conditions. The relationships of these indices with proteinuria and progression of renal disease are not well known. This study aimed to assess PLT indices in patients with primary glomerular nephrotic range proteinuria (PGNRP), with and without chronic kidney disease (CKD), and to compare these indices with those of healthy individuals (His). Methods This cross-sectional study was performed from January 2015 to May 2015. HIs (n = 57) and patients with PGNRP (n = 41) were enrolled. PLT indices and blood biochemistry parameters were compared between HIs and patients with PGNRP, as well as between subgroups of patients with PGNRP who had CKD (n = 23) and those who did not have CKD (n = 18). Results There were no statistically significant differences in any PLT indices (i.e., platelet number, mean platelet volume, plateletcrit, and platelet distribution width) between HIs and patients with PGNRP, or between the subgroups of patients with PGNRP. However, patients with PGNRP who had CKD exhibited higher median C-reactive protein and mean albumin levels, compared with patients who did not have CKD. Conclusions Pathological processes in proteinuria and CKD are not associated with PLT indices.
Keywords: Platelet indices; primary glomerular disease; nephrotic range proteinuria; chronic kidney disease; platelet count; mean platelet volume; plateletcrit; platelet distribution width; C-reactive protein; serum albumin